HIF-1α- Targeting Acriflavine Provides Long Term Survival and Radiological Tumor Response in Brain Cancer Therapy. Issue 1 (December 2017) - Mangraviti, Antonella; Raghavan, Tula; Volpin, Francesco; Skuli, Nicolas; Gullotti, David; Zhou, Jinyuan; Asnaghi, Laura; Sankey, Eric; Liu, Ann; Wang, Yuan; Lee, Dong-Hoon; Gorelick, Noah; et al.
Abstract Tumor progression, limited efficacy of current standard treatments, and the rise in patient mortality are associated with gene expression caused by the synergistic action of intratumoral hypoxia and HIF-1α activation. For this reason, recent investigations have focused on HIF-targeting therapeutic agents, with encouraging preclinical and clinical results in solid tumors. Here we describe the efficacy of a HIF-1α inhibitor, Acriflavine, and demonstrate its potency against brain cancer. This safe antibacterial dye induces cell death and apoptosis in several glioma cell lines, targets HIF-1α–mediated pathways, and decreases the level of PGK1, VEGF and HIF-1αin vitro andin vivo . Administered locally via biodegradable polymers, Acriflavine provides significant benefits in survival resulting in nearly 100% long term survival, confirmed by MRI and histological analyses. This study reports preclinical evidence that this safe, small molecule can contribute to brain tumor therapy and highlights the significance of HIF-1α-targeting molecules.